Glutathione-responsive multifunctional nanoparticles based on mannose-modified pillar[5]arene for targeted antibiotic delivery against intracellular methicillin-resistant S. aureus. (6th January 2022) - Peng, Haibo; Xie, Beibei; Cen, Xianfeng; Dai, Jiaojiao; Dai, Yuanwei; Yang, Xiaohong; He, Yun
Abstract : GSH-responsive multifunctional antibiotic delivery system (WP5⊃G) was successfully developed. WP5⊃G could encapsulate linezolid (LZD) to form drug-loaded nanoparticles (LZD-WP5⊃G), improving the anti-intracellular MRSA activity of LZD with excellent biocompatibility. Abstract : MRSA can evade the immune system once they are engulfed by phagocytic host cells. This protects them against the bactericidal action of antibiotics and allows the infection to remain latent or to recur. In this work, a glutathione (GSH)-responsive multifunctional antibiotic delivery system (WP5 ⊃ G) based on the host–guest interaction between mannose-modified pillar[5]arene (WP5) and a near-infrared (NIR) fluorescence receptor (G) was successfully developed. WP5 ⊃ G could encapsulate hydrophobic antibiotics such as linezolid (LZD) to form drug-loaded nanoparticles (LZD–WP5 ⊃ G), improving the anti-intracellular MRSA activity of LZD with excellent biocompatibility. This easily prepared and flexible system could be employed for simultaneous non-invasive cellular imaging and real-time monitoring of antibiotic release, representing a novel strategy toward targeted antibiotic delivery into macrophages for treating intracellular bacterial infections.